MODEL IKATAN HUBUNGAN, NILAI PELANGGAN TERHADAP LOYALITAS NASABAH PADA BANK PEMERINTAH DI JAWA TENGAN - Naili Farida (Jurnal Keuangan dan Perbankan, 2010)
The study discussed about the integration of relational bonding, relational quality,on service quality and customer loyalty at the state-owned bank in Central Java. The loca-tions of research included Semarang City, Surakarta City, and Cilacap City. Research methodused multi stage sampling. The sample of research counted 278 customers of Regular Savingfrom Bank Negara Indonesia (BNI), Bank Mandiri, Bank Rakyat Indonesia, Bank TabunganNegara, and Bank Pembangunan Central of Java. The hypothesis test in this research em-ployed descriptive analysis and Structural Equation Modeling (SEM). The descriptive analysishad loading factor and 5 % significance rate. The objective of research was to understandand to analyze the relational bonding between the Bank customers through corporate im-age, customer value, and relational quality as well as service quality on customer loyalty. Thestate-owned banks in Central Java already used this model. Result of research, related to theresult of SEM analysis, indicated that the relevancy of relational bonding, corporate image,customer value, and service quality had significant effect on customer loyalty. Therefore, thismodel should be developed by the state-owned banks to increase the customer loyalty.